Hubungan Kepemimpinan, Kompensasi dan Kompetensi terhadap Kinerja Pegawai Toserba Yogya Sukabumi - Wieke Tsanya Fariati (LP2M CBI PRESS, 2019)
This research is intended to evaluate and measure the relationship of leadership, compensation, and competency with performance. The research object is health agency in Sukabumi, West Java. There are 95 persons as staffs onhealth agency.Respondents were recruited from this population using stratified random sampling. As variables are latent in nature,questionnaire was used as research instrument. Further, data collected was analyzed using regression equation by deployed SPSS (Statistical Package for Social Science)software. Result indicates that leadership, competency, and compensation aresignificantly influence staff performance. The correlation of leadership with staff performance is 0.102. The correlationbetween compensation and staff performance is 0.104. And the last, the correlation between competency and staff performance is 0.13. It is also shown that leadership, compensation, and competency can explain staff performance variation as much as 48.8%.